Environmental Variation and Correlation of Seed Components in Nontransgenic Soybeans: Protein, Oil, Unsaturated Fatty Acids, Tocopherols, and Isoflavones - Carrera, Constanza Soledad (2011)
The environment has a significant influence on the expression of traits contributing to soybean nutritional and/or industrial value. The aim of this study was to explore and describe the variability of nontransgenic soybean seed chemical components by investigating the environmental correlations among protein (Pr), oil (O), oleic (Ol), linoleic (La), and linolenic (Ln) acids, oleic to linolenic acid ratio (Ol:Ln) alpha- (AT), beta- (BT), gamma- (GT), delta- (DT), and total tocopherols (TT) and total isoflavones (TI) by means of principal component analysis. We analyzed seeds from multienvironment trials involving 23 field trials grown in Argentina (24 to 38° S latitude). A wide range of variability was observed for Ol, Ln, Ol:Ln, AT, BT, and TI. The strongest environment-induced relationships found were the negative correlation between DT and AT and the positive correlation between DT and Ln. Increased Ol:Ln was negatively correlated with Ln. High values of DT, Ln, and Pr were associated with cool environments, TI content was greater in temperate to cool environments, and AT, O, and Ol:Ln were associated with warm environments. Warm environments would be suitable for obtaining products with higher O concentration of low oxidation capacity and greater vitamin E content. In turn, temperate to cool environments would be suitable for the production of soybean with higher TI, La, Ln, and TT content; in addition, these environments would favor seeds of higher Pr concentration.